2022
DOI: 10.3390/app12126124
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Various Cementing Agents on Occlusal Discrepancy Using an Intra-Oral Scanner: An In Vivo Study

Abstract: A marginal fit of all-ceramic crowns is a prerequisite for the long-term clinical success of a dental restoration. Few in vivo studies have investigated the effect of the film thickness of various luting agents on vertical discrepancy. This in vivo study evaluated the influence of three luting cements on the occlusal vertical discrepancy of milled crowns using a complete digital workflow. Forty-three patients treated in a students’ clinic in Tel-Aviv University with 45 single posterior digitally prepared monol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Their study included the newest generations of milled dental ceramics, such as those made of LD, from various manufacturers. Thus, it was concluded that although the mean marginal gap of the IPS E-Max milling crowns (Ivoclar Vivadent AG, Schaan, Liechtenstein) of 49.2 µm was statistically significantly greater than those of all others, this threshold is among the clinically acceptable mean maximum gap of less than 120 µm [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Their study included the newest generations of milled dental ceramics, such as those made of LD, from various manufacturers. Thus, it was concluded that although the mean marginal gap of the IPS E-Max milling crowns (Ivoclar Vivadent AG, Schaan, Liechtenstein) of 49.2 µm was statistically significantly greater than those of all others, this threshold is among the clinically acceptable mean maximum gap of less than 120 µm [36,37].…”
Section: Discussionmentioning
confidence: 99%